If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5 = 2(3x + -6) Reorder the terms: -5 + 3x = 2(3x + -6) Reorder the terms: -5 + 3x = 2(-6 + 3x) -5 + 3x = (-6 * 2 + 3x * 2) -5 + 3x = (-12 + 6x) Solving -5 + 3x = -12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -5 + 3x + -6x = -12 + 6x + -6x Combine like terms: 3x + -6x = -3x -5 + -3x = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 -5 + -3x = -12 + 0 -5 + -3x = -12 Add '5' to each side of the equation. -5 + 5 + -3x = -12 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = -12 + 5 -3x = -12 + 5 Combine like terms: -12 + 5 = -7 -3x = -7 Divide each side by '-3'. x = 2.333333333 Simplifying x = 2.333333333
| 4x-2(x-2)=-8+4x+6 | | 10p-95=p+31 | | 6(x-5)=5 | | .27(x+2)=42 | | 9a=9a | | 125+x+15=180 | | 3x+-2=4x+5 | | -42y=66 | | 42y=66 | | -8x-5y=-11 | | 81-x=27 | | 9a=a+60 | | 2b-b^2-15=0 | | 2(2x-8)-5=2(x-3)-1 | | 78507+11.25x=20885+23x | | 6N+6J=N | | 2a-11=3(a+1)+16a+5 | | 3x^2-13w-6w^2=0 | | v=2v-73 | | 7n+6=13+7n | | 16=-2(x+4) | | 5-13w-6w^2=0 | | 4u+18=2u+66 | | 0.20=ln(y) | | .25(x+4)=32 | | 9x^2-36=y | | 8u^2+1u-9=0 | | 28-8k=4(-1-k) | | 6x+-9=2x+7 | | 17x-7=13x+1 | | 6x+-9=2x+-7 | | 3.2=y+5.4 |